REFORM OF THE MANAGEMENT SYSTEM IN THE FIELD OF UZBEKISTAN RAILWAYS (International Congress on Economics, Management and Business Studies, 2026)
This article covers the changes in the management system of the railway sector of the Republic of Uzbekistan and the reforms implemented in this regard, as well as the complex processes in the railway sector in the early years of independence.
Keywords: Industrial, construction, trade and supply enterprises, public education and healthcare institutions, transportation of goods, passengers, mail and baggage, Andijan station, denationalization.